How to improve outcome in nephron-sparing surgery: the impact of new techniques. Issue 3 (May 2021) - Cignoli, Daniele; Fallara, Giuseppe; Larcher, Alessandro; Rosiello, Giuseppe; Montorsi, Francesco; Capitanio, Umberto
Abstract : Purpose of review: Nephron-sparing partial nephrectomy is the state of the art for localized small renal mass and it is gaining attention also for more advanced cases. In the present narrative review, we discuss the new developments that have occurred in the advancement of this approach over the past few years. Recent findings: Off-clamp, selective/superselective clamp and early-unclamping techniques are safe and feasible approaches, with potentially superior functional outcomes, and noninferior complications rate and oncological outcomes, when compared with main artery clamping. Renorrhaphy must preserve the physiological vascularization of residual parenchyma. Running sutures, particularly using barbed wires, shorten the operating and ischemia times. A further advantage could derive from avoiding a double-layer suture. Transperitoneal robot-assisted partial nephrectomy (RAPN) and retroperitoneal RAPN can be considered equivalent in terms of perioperative morbidity, functional and oncologic outcomes, regardless of tumor's location, thus the choice of the approach should be driven by the surgeon's expertise. Future improvements should be introduced by the single-port robotic surgery, which seems to be safe and feasibly also in an off-clamp manner. Summary: Significant advances have recently been achieved in nephron-sparing surgery technique. However, future studies with standardized reporting of these new techniques are needed to assess the real impact of them on early and long-term functional outcomes.